On Two Old Russian Inscriptions from Belarus and Poland - Mikheev, Savva M. (Slověne, 2015)
Two Old Russian graffiti inscriptions are examined in the present paper. The first one, dating back to the late 13th–early 14th centuries, is located on one of the walls of the Savior Transfiguration Church in the St. Euphrosyne convent in Polotsk, Belarus. It reads Marъkova žana dobra ‘Mark’s wife is good.’ The second graffito was inscribed on a knife handle excavated in Drohiczyn, Eastern Poland (Old Russian Dorogyčinъ), and dates to the end of the 11th through the 12th centuries. The inscription reads Ežьkovъ nožь a iže i ukradetь proklętъ . . . ‘Ezhko’s knife. Whoever steals it, be cursed . . .’ Although both inscriptions have been published, the present study adds more in-depth paleographic and linguistic commentary and suggests corrected readings. The laudatory inscription from Polotsk is particularly interesting because it contains an early example of a spelling reflecting yakanye, a trait of Belarusian phonetics, whereas the interest of the Drohiczyn inscription lies in its unusual paleographic features.